IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU NOMOR 8 TAHUN 2012 TENTANG RETRIBUSI IZIN GANGGUAN (STUDI KASUS USAHA PETERNAKAN AYAM DAN BABI DI PEKANBARU) - Ramadhani, melisa; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Place chicken and pig farm established in Pekanbaru are still many who do not have permission, especially where the business is located adjacent to residential areas that cause odor and very disturbing comfort of the community around the business premises. Supposedly every effort it must have become a nuisance permit the replacement for the location permit that every effort that has strong legal powers. The purpose of this research is to determine and analyze the implementation and the factors that affect the implementation of Pekanbaru City Regulation No. 8 of 2012 on Disturbance Permits.The theory used is the theory of policy implementation according to Van Meter and Van Horn, in theory this implementation there are six variables: standards and policy targets, Resources, Managing Organizational Characteristics, Attitudes of the Executive, Organizational Communication between related and implementing activities, social environment, economic and political. The method used in this study is a qualitative method using triangulation techniques. In this study, the research informants is the Dinas Pertanian Bidang Peternakan, Badan Pelayanan Terpadu dan Penanaman Modal (BPTPM) dan Satpol PP Kota Pekanbaru.Based on the research that has been done can be concluded that the implementation of Regional Regulation No. 8 of 2012 Pekanbaru Licenses Disorders (Business Case Studies Poultry and Pig) is not going well. This is evidenced by the many efforts of chicken and pig farms that do not have the permission due to a lack of awareness of the policy implementers, lack of good communication between satpol pp, BPTPM dan dinas pertanian bidang peternakan, human resources are lacking in Dinas Pertanian Bidang Peternakan which causes a lack of team to go down spaciousness, and socialization performed by actors of government to the people did not go well that caused widespread public ignorance of the existence of regional regulation.Keywords: Implementation, Disturbance Permit, Poultry and Pig